The Poda Na Lima philosophy: A contextual leadership framework for elementary schools - Tanggapan C. Tampubolon; Kaleb E. Simanungkalit (Indonesian Journal of Educational Development (IJED), 2026)
This study reconstructs the Poda Na Lima philosophy into a contextual school leadership framework to bridge the gap between formal administrative demands and local cultural values. The objective is to analyze how these indigenous values are interpreted and implemented by school principals in North Tapanuli. Using a qualitative exploratory design, the study employed purposive sampling to select 15 participants (3 principals, 9 senior teachers, and 3 community leaders) from the elementary school population. Data were gathered through in-depth interviews, field observations, and document analysis. Results indicate that Poda Na Lima encompasses five dimensions: leadership accountability, teacher professionalism, infrastructure management, environmental development, and social ethics. These values are operationalized through transparency, role modeling, and ethical communication within the school community. In conclusion, integrating indigenous wisdom fosters a contextual leadership model that strengthens school governance and social harmony. It is recommended that local education authorities integrate this framework into leadership training programs to enhance culturally-responsive school management.